1999
DOI: 10.1021/la9812929
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Azimuthal Tilt Order in Monolayers by Liquid Crystal Optical Amplification

Abstract: Monolayers of the amphiphile 1-monopalmitoyl-rac-glycerol at the air−water interface assemble into domains in which the molecular tilt azimuth is organized into star-shaped patterns. When the domains are transferred to solid supports as Langmuir−Blodgett films, they are capable of producing a macroscopic azimuthal orientation of nematic liquid crystals, which allows the order in the monolayer to be observed by polarized optical microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…In ref. 22, we showed that the variation of the molecular tilt direction in the Langmuir monolayer of 1-monopalmitoyl-rac-glycerol can induce an azimuthal orientation in nematic liquid-crystal layers. After the liquid-crystal optical amplification, the tilted textures in the monolayer can be easily visualized with a polarizing optical microscope.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In ref. 22, we showed that the variation of the molecular tilt direction in the Langmuir monolayer of 1-monopalmitoyl-rac-glycerol can induce an azimuthal orientation in nematic liquid-crystal layers. After the liquid-crystal optical amplification, the tilted textures in the monolayer can be easily visualized with a polarizing optical microscope.…”
mentioning
confidence: 87%
“…In recent years, there has been an increased interest in developing an imaging technique based on liquid-crystal optical amplification for studying the structures and physical properties of organic and biological interfaces (21)(22)(23)(24)(25). It has been demonstrated that liquid crystals can map differences in the spatial orientation of terminal groups in self-assembled monolayers (SAMs) formed from alkanethiols that differ by single methylene (21).…”
mentioning
confidence: 99%
“…Thus, optical properties of the LC can be used as a tool to investigate molecular order in the interfacial layer. 6 Anchoring orients the LC director at the boundary of interest and is defined by two angles: zenithal and azimuthal ( Figure 1). 7 The zenithal angle may be planar (director aligned parallel to the interface), homeotropic (director aligned perpendicular to the interface), or tilted (director aligned at an intermediate angle).…”
Section: Introductionmentioning
confidence: 99%
“…These films are previously self-assembled at the air/water interface [18], where they organize into isolated sub-millimeter circular islands featuring polar nematic order with the elongated molecules anchored at a fixed angle of the interface normal (~ 45º), and a tilt orientation tangential to the circular boundary (s = +1, c = π/2), which results in a selectable orientational chirality [19]. In contact with the LB-coated glass substrate, LC molecules follow the local in-plane orientation of the amphiphilic molecules in the monolayer [20]. This procedure, in which LC molecules are aligned by self-assembled patterns featuring a well-defined and robust tilt-orientational order in a monolayer of uniform thickness, is in contrast to other patterning techniques based on mechanical [21] or optical [22] modification of a polymer layer, which lacks a similar degree of order.…”
mentioning
confidence: 99%